PENGARUH KINERJA KEUANGAN TERHADAP STRUKTUR MODAL - Euis Bandawaty; Nugraha Nugraha; Disman Disman; Maya Sari (Media Ekonomi, 2023)
Capital structure is an important aspect of the development of a company; insufficient capital makes it difficult for the company to develop business activities. Capital structure is also closely related to various aspects, such as investors. This condition makes the capital structure position an important part of the company's ability to carry out company activities. The capital structure that becomes the focus of managers and investors in various previous studies is caused by various factors, such as profitability, corporate tax, and corporate liquidity. The purpose of this study is to examine the effect of financial performance on capital structure. This research uses a quantitative approach that focuses on INAF companies during 2010–2020. The data analysis method used in this research is an analysis by comparing emerging market countries with developed market countries. The result shows that the lower the profitability, the higher the capital structure, which indicates that the company increases the capital structure when the profitability decreases. Corporate tax in this study indicates that with a higher corporate tax, the capital structure also increases. This indicates that a high tax encourages the company to increase its capital structure. Liquidity in the research shows no influence, so liquid and not-liquid companies are not factors that cause changes in capital structure.